pH responsive graft copolymers of chitosan - Yilmaz, Elvan; Yalinca, Zulal; Yahya, Kovan; Sirotina, Uliana (Elsevier, 2016)
Grafting suitable polymers onto chitosan can produce cationic or polyampholyte polymers or hydrogels that are potential smart biomedical materials. Chitosan-graft-[poly(diethylamino)ethyl methacrylate] has been prepared in three different physical forms as linear free chains in solution, chemical gels crosslinked with glutaraldehyde, and poly(diethylamino)ethyl methacrylate] grafted onto chitosan tripolyphosphate gel beads. In addition to chemical structure, the graft copolymers were characterized with respect to their dissolution and swelling behavior in aqueous solution. It has been established that solubility of the products is controlled by the grafting yield. While pH sensitive polymers, which collapse at a given pH value are obtained at lower grafting yields, hydrogels form at higher grafting yields with pH responsive swelling behavior. Glutaraldehyde crosslinked chitosan-graft-[poly(diethylamino)ethyl methacrylate] gels and chitosan tripolyphosphate gel beads grafted with poly[(diethylamino)ethyl methacrylate] exhibit pH sensitive swelling with highest equilibrium swelling capacity at pH=1.2. (C) 2015 Elsevier B.V. All rights reserved.
International Biomedical Engineering Congress -- 2015 -- Near E Univ, North Nicosia, CYPRUS
Keywords: Chitosan; Polymethacrylate; Environment responsive polymer